Applications of Machine Learning (ML) - The real situation of the Vietnam Fintech Market - Hoang Duc Le; Giang Huong Nguyen; An Thuy Bui; Trang Quynh Le; Trang Ha Nguyen (Celebes Scholar pg, 2022)
Machine Learning (ML) is a well-known term in the technological field. However, using ML models in financial institutions is a matter of concern. In fact, the 4.0 Industry has encouraged them to expand their digital system to bring the best experience for their clients. This journal will discuss the definition and applications of ML, the actual situation of the Vietnam Finetech Market. Thereby, we will make predictions about the future of financial institutions, which determines them to use ML in their activities.